2021
DOI: 10.1016/j.soard.2021.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 and myeloid differentiation factor 88 are required for gastric bypass-induced metabolic effects

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Furthermore, deletion of the TLR4-receptor or MYD88 in mice reduced the effects of RYGB on glycemic control. Immune-signaling via TLR4 receptors and myeloid-differentiation factor 88 (MyD88) may be one of the underlying signaling pathways, as deletion of their function resulted in a partial loss of beneficial effects of the surgery on metabolism at 5 weeks after surgery [ 253 ]. However, these conclusions are tempered by the fact that the TLR4-KO mouse has a lean phenotype that should make it largely resistant to the body weight-lowering effects of RYGB [ 253 ].…”
Section: Major Candidate Mechanisms For the Effects On Body Weightmentioning
confidence: 99%
“…Furthermore, deletion of the TLR4-receptor or MYD88 in mice reduced the effects of RYGB on glycemic control. Immune-signaling via TLR4 receptors and myeloid-differentiation factor 88 (MyD88) may be one of the underlying signaling pathways, as deletion of their function resulted in a partial loss of beneficial effects of the surgery on metabolism at 5 weeks after surgery [ 253 ]. However, these conclusions are tempered by the fact that the TLR4-KO mouse has a lean phenotype that should make it largely resistant to the body weight-lowering effects of RYGB [ 253 ].…”
Section: Major Candidate Mechanisms For the Effects On Body Weightmentioning
confidence: 99%
“…The diversity of the composition of different microbial colonies contributes to and is associated with various metabolic disorders such as atherosclerosis. Low levels of Bacteroidota and intestinal dysbiosis of opportunistic pathogens such as Enterobacter, Collinsella, Desulfovibrio, and Klebsiella genera are factors associated with atherogenesis and atherosclerotic plaques [ 29 , 46 , 56 ] Furthermore, apart from their absolute number, the relative ratio between them is also of great importance, which also plays a role in metabolic diseases. It has been reported that Bacteroidota play an important role in regulating the actions of T cells and, by extension, the body′s immune system [ 46 , 56 , 57 , 58 , 59 ].…”
Section: Gut Microbiota Dysbiosis and Atherosclerosismentioning
confidence: 99%
“…Low levels of Bacteroidota and intestinal dysbiosis of opportunistic pathogens such as Enterobacter, Collinsella, Desulfovibrio, and Klebsiella genera are factors associated with atherogenesis and atherosclerotic plaques [ 29 , 46 , 56 ] Furthermore, apart from their absolute number, the relative ratio between them is also of great importance, which also plays a role in metabolic diseases. It has been reported that Bacteroidota play an important role in regulating the actions of T cells and, by extension, the body′s immune system [ 46 , 56 , 57 , 58 , 59 ]. In addition, infections by Helicobacter pylori are associated with an increased atherogenic profile, due to lipopolysaccharide (LPS), which characterizes this genus of microbes and their ability to cause vascular inflammation.…”
Section: Gut Microbiota Dysbiosis and Atherosclerosismentioning
confidence: 99%
“…TLR4 expression in patients with NAFLD is associated with fibrosis (Vespasiani-Gentilucci et al, 2015). It has been shown that RYGB specifically reduces TLR4 expression in the small and large intestines of C57Blc/6J mice, and that TLR4 and myeloid differentiation factor 8 (MyD88, a key downstream signaling regulators) are required for RYGB-induced metabolic responses (Abu El Haija et al, 2021).…”
Section: Reversing Inflammationmentioning
confidence: 99%